Guiding Value of Circulating Tumor Cells for Preoperative Transcatheter Arterial Embolization in Solitary Large Hepatocellular Carcinoma: A Single-Center Retrospective Clinical Study - Zhang, Qiao; Xia, Feng; Mo, Ali; He, Weiming; Chen, Jiazhen; Zhang, Weiqiao; Chen, Weiqiang (Frontiers in Oncology, 2022)
BACKGROUND: Large hepatocellular carcinoma（LHCC）is highly malignant and prone to recurrence, which result in poor long-term prognosis for patients, so relevant measures are urgently needed to intervene against postoperative recurrence. Preoperative Transcatheter Arterial Embolization（TACE）is an effective treatment. But reliable preoperative indicators to guide the application of preoperative TACE are currently lacking. Thus, we investigated whether the pre-operative status of circulating tumor cells (CTCs) could be used to guide preoperative TACE for HCC treatment. METHODS: This study enrolled 361 HCC patients and compared recurrence-free survival（RFS） and overall survival （OS）between patients who received TACE before surgery and those who did not. Patients were divided into CTC-positive and CTC-negative groups according to CTCs status, and the effects of preoperative TACE on RFS and OS were compared in each subgroup. RESULTS: In CTC-positive patients, preoperative TACE reduces early recurrence and improves long-term survival. But, for the overall population and CTC-negative patients, HCC patients did not benefit from preoperative TACE. CONCLUSIONS: Preoperative CTC detection is a reliable indicator that can be used to predict whether HCC patients received TACE preoperatively. CTC positivity was associated with early tumor recurrence, and preoperative TACE could reduce early recurrence and long-term prognosis in CTC-positive patients.